Definitive Obturator Prosthesis Post Mandibular Dredging for Treatment Ameloblastoma Patient: A Case Report - Faizal Fachry, Muhammad; Anshori, Nuriani; Awaliyah, Rizkiani; Hastinawaty,; Mirna Nasliah, Andi; Dharma Utama, Moh; Nurrahma, Rifaat (Gaceta Médica de Caracas, 2024)
Background: Ameloblastoma is an odontogenic tumor that can cause bone destruction in the mandible. Mandibular dredging is a conservative treatment that involves enucleation and curettage of tumor tissue to remove tumor tissue from the bone-tooth loss after mandibular dredging treatment results in reduced occlusion function and aesthetics. A definitive obturator prosthesis is helpful to restore occlusions and aesthetics.